Increasing the intention of Gen Zers to adopt drone delivery services based on a three-step decision-making process - Charlie Chen; Makoto Nakayama; Peter Ractham (Cogent Business & Management, 2023)
Generation Zers are digital natives who may be early adopters of drone delivery services for e-commerce. Therefore, e-commerce vendors must understand what causes Gen Zers to believe, desire, and intend to adopt drone delivery services. Gen Zers were surveyed regarding their decision-making processes using the DITTO research framework (Diversity, Individualism, Teamwork, Technology, and Organizational Support) and belief-desire-intention theory. A survey was conducted with 83 Gen Zers from the United States, and data was analyzed using multilinear regression analysis. Many important implications can be drawn from the analysis results. Before Gen Zers adopt drone delivery services, the "seeing is believing" moment appears to be essential, according to the analysis. Moreover, e-commerce vendors should emphasize drone delivery's relative advantages in terms of speed and environmental protection. Based on our findings, Gen Zers are rational decision-makers when it comes to adopting drone delivery services. To motivate Gen Zers to use drone delivery services, it is imperative to help them develop the belief and increase their desire.
Keywords: 650; Drone Delivery; E-Commerce; Generation Z; Last Mile Delivery